'Hidden' occupational allergens such as additives. Issue 2 (April 2018) - Quirce, Santiago; Antolín-Amérigo, Darío; Domínguez-Ortega, Javier
Abstract : Purpose of review: With the development of innovative technologies, new agents are continually introduced to the workplace. Some of these agents can act as hidden allergens whenever they are not declared in the product labels or whenever their health hazards are unknown. This review article focuses on the identification and description of unusual and/or hidden allergens recently incriminated in occupational diseases. Recent findings: Occupational exposure is an important global health issue that can induce respiratory and cutaneous disorders, as well as life-threatening anaphylaxis. Apart from the classic forms of occupational exposure, reports have emerged from nonconventional or newly identified allergens or additives. These compounds are substances added to another in order to alter or improve the general quality or to counteract undesirable properties, and some of them may behave as potent and frequently hidden allergens. These highly uncommon and/or hidden allergens belong to several categories: foods, spices, cosmetics, insects, enzymes, chemicals, drugs, preservatives, and coloring agents, among others. Summary: A high level of suspicion and awareness about the potential hidden allergens is necessary to ascertain the allergens implicated. It is of utmost importance to identify the specific eliciting agents of the occupational diseases in order to avoid strictly further exposure to them.